2008
DOI: 10.1136/bmj.a438
|View full text |Cite
|
Sign up to set email alerts
|

Academic achievement of twins and singletons in early adulthood: Taiwanese cohort study

Abstract: Objectives To examine the long term effects of low birth weight on academic achievements in twins and singletons and to determine whether the academic achievement of twins in early adulthood is inferior to that of singletons. Design Cohort study. Setting Taiwanese nationwide register of academic outcome. Participants A cohort of 218 972 singletons and 1687 twins born in Taiwan, 1983-5. Main outcome measure College attendance and test scores in the college joint entrance examinations. Results After adjustment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
35
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 24 publications
6
35
2
1
Order By: Relevance
“…Early postnatal catch-up growth may require more energy thereby draining resources from neural development and consequently have a negative influence on the cognitive development. Other studies of twins propose that part of the positive association between birthweight and IQ may be mediated through genetic effects and consequently noncausal (Boomsma et al, 2001;Tsou et al, 2008).…”
Section: Abstract: Twins Academic Performance Genetic Mediation Bimentioning
confidence: 99%
See 2 more Smart Citations
“…Early postnatal catch-up growth may require more energy thereby draining resources from neural development and consequently have a negative influence on the cognitive development. Other studies of twins propose that part of the positive association between birthweight and IQ may be mediated through genetic effects and consequently noncausal (Boomsma et al, 2001;Tsou et al, 2008).…”
Section: Abstract: Twins Academic Performance Genetic Mediation Bimentioning
confidence: 99%
“…A Dutch study of 170 twin pairs tested 4 times in the age range 5-12 found a significant positive association between differences in birthweight and differences in IQ at age 7 and at age 10 within DZ pairs, but no similar associations within MZ pairs (Boomsma et al, 2001). In a recent study of 316 same-sex and 61 opposite-sex Taiwanese twin pairs (Tsou et al, 2008), the authors found a positive within-pair association birthweight and both mathematics and English test scores in opposite-sex twin pairs but not in same-sex twin pairs; the authors did not have access to zygosity information. Failure to observe within pair associations between measures of cognitive functioning and birthweight in MZ pairs in the Dutch study (Boomsma et al, 2001) and same-sex pairs in the Taiwanese study (Tsou et al, 2008) led the researchers to conclude that their results imply that the birthweight-IQ association is partly due to genetic confounding, that is, that common genetic factors are influencing both fetal growth and IQ.…”
Section: Abstract: Twins Academic Performance Genetic Mediation Bimentioning
confidence: 99%
See 1 more Smart Citation
“…However, the findings of the Tsou et al (2008) study are not consistent with those of a similar population-based study conducted in Denmark (Christensen et al, 2006). The Danish study compared academic performance of adolescent twins and singletons (age 15 or 16) born between 1986 and 1988 and reported that differences in academic performance between the two groups were negligible after the data were adjusted for various confounding factors such as birth weight and gestational age.…”
mentioning
confidence: 65%
“…Only a few studies have looked at the differences in educational achievement between twins and singletons. A 1983-1985 birth cohort study from Taiwan found that twins had lower scores and were less likely to attend college, even when the data were adjusted for birth weight, gestational age, birth order within the family, sex, and socioeconomic status (Tsou, Tsou, Wu, & Liu, 2008). The scores of Dutch female twins on an educational achievement test were also lower than those of singleton controls from the the same grade and those of an older brother or sister.…”
mentioning
confidence: 99%